Climate change, nature degradation, and financial stability: a review of domino-effects between finance, climate, and the biosphere - Paula A. Sánchez-García; Victor Galaz; Juan C. Rocha; Felix Barbour (Ecology and Society, 2025)
The threat associated with climate change and nature degradation poses complex financial challenges. Our systematic literature review of 88 finance-related publications published between 2015 and early 2022 revealed a gap in research on nature-related financial risks and their connections to climate change, particularly regarding ocean-related risks beyond rising sea levels. Although methods are available to assess these risks, more standardized approaches are needed. Based on this literature review, we developed a typology of climate-nature-finance effects using nine nested causal loop diagrams (CLDs). Our typology illustrates how climate change and environmental degradation can create chain reactions or domino-effects impacting insurance coverage, investors’ confidence, and market stability, leading to broader economic instability. This typology can help practitioners and scholars analyze their exposure to climate change and ecological degradation. Additionally, it can contribute to developing alternative quantitative assessments for studying non-linearities in financial risks. Future research can benefit from addressing the interactions between climate change and nature degradation more effectively and exploring the effects of finance on the environment and society.